Edukasi dan Pelatihan Pembukuan Sederhana pada UMKM Makanan di Kecamatan Kramatwatu - Kodriyah, Kodriyah; Mahardini, Nikke Yusnita; Suhartini, Suhartini (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: The purpose of this PKM activity is to provide education, understanding and knowledge about financial management and provide simple bookkeeping training to MSME actors in Kramatwatu District Research Methodology: This PKM activity is carried out in three stages, namely preparation including observation activities, preparing activity administration, designing activities, the second stage is implementation including preparing activity schedules, providing financial management education activities and providing simple bookkeeping training, the third stage evaluating through reflection on the results of changes that occur from this PKM activity Results/findings: This PKM activity can motivate MSME actors to continue to develop to achieve their goals, provide knowledge and understanding of the importance of managing finances, separate personal finances from business finances, be able to compile regular expenditure budgets, be able to identify financial positions, realize that no matter how small a business must continue to do bookkeeping, using special books, namely purchase books, sales books, accounts receivable books, debt books and cost books, Business actors do bookkeeping and prepare financial statements Limitation: The limitations of this PKM activity have not accommodated all MSME business actors because the object of this activity is food business actors Contribution: This PKM has major implications for the financial management and bookkeeping of MSME actors in Kramatwatu District, where partners feel helped to advance and develop their business by looking at financial statements as a reflection of their business conditions.